2017
DOI: 10.1111/1750-3841.14006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Long‐Term Intake of Phenolic Compounds‐Rich Grape Pomace on Rat Gut Microbiota

Abstract: The aim of this work is to evaluate the impact on the rat microbiota of long-term feeding with phenolic compounds (PC) rich grape pomace extracts. Thirty, 2-mo-old rats, were divided into 5 groups. Four groups were treated with different concentrations of PC (2.5, 5, 10, and 20 mg/kg/d diluted in 0.1% DMSO), and 1 group received 0.1% Dimethyl Sulfoxide (DMSO) alone (control group). The daily treatment lasted 14 mo. Major phenolic compounds constituents were characterized by the high-performance liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 40 publications
3
50
0
2
Order By: Relevance
“…Similarly, herein, the Firmicutes phylum was decreased in a significant way (p < 0.05) under DSS effect and was not affected by the addition of GSM into the diet in a significant way. Clostridium, Roseburia, Acidaminococcus, and Escherichia are often cited as the genera usually found in abundance in irritable bowel diseases (48)(49)(50)(51)(52) and DSS treatment, while Lactobacillus, Prevotella, and Faecalibacterium are cited as negatively impacted or inversely correlated with the severity of the disease (33,(53)(54)(55)(56). Indeed, in our work, Roseburia, Megasphera, and CF231 increased significantly under the DSS presence while Lactobacillus registered a significant decrease overall.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Similarly, herein, the Firmicutes phylum was decreased in a significant way (p < 0.05) under DSS effect and was not affected by the addition of GSM into the diet in a significant way. Clostridium, Roseburia, Acidaminococcus, and Escherichia are often cited as the genera usually found in abundance in irritable bowel diseases (48)(49)(50)(51)(52) and DSS treatment, while Lactobacillus, Prevotella, and Faecalibacterium are cited as negatively impacted or inversely correlated with the severity of the disease (33,(53)(54)(55)(56). Indeed, in our work, Roseburia, Megasphera, and CF231 increased significantly under the DSS presence while Lactobacillus registered a significant decrease overall.…”
Section: Discussionsupporting
confidence: 51%
“…The observed reduction in the abundance of Lactobacillus spp. in pigs with DSSinduced inflammation or pigs with an intake of GSM diet and dramatically in DSS+GSM groups might be associated with the negative impact that the DSS has on this genus (55) as well as the interaction between Lactobacillus, the type of phenolic compounds and their concentration as described in the scientific literature (56,60). However, the findings are controversial.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The corresponding by‐products were stored at −20°C until use. Once defrosted at room temperature, PC extraction and characterization were performed as previously described (Chacar et al, ). Briefly, the PC were extracted from grape pomace extracts via a solid–liquid extraction, and then, the solutions were spray‐dried and we obtained a powder consisting of a pure mixture of PC.…”
Section: Methodsmentioning
confidence: 99%
“…Absorption and metabolism of phenolic acids also take place in the large intestine, where the microbiota plays an important role in further catabolizing and modifying the precursor compounds (Anhê et al, 2013;Olthof, Hollman, Buijsman, van Amelsvoort, & Katan, 2003). Some in vitro and in vivo studies have shown the potential prebiotic effects of phenolic acids to increase the population of healthy beneficial bacteria such as bifidobacteria whilst decreasing adverse populations (Chacar et al, 2018;Duncan et al, 2016;Xie et al, 2017). Thus the resulting metabolic end products from the large intestine are likely to be quantitatively more important contributors to the circulating levels of physiologically relevant metabolites than those from the small intestine and contribute to a later peak of CGAs in the blood (Gonthier et al, 2003;Renouf et al, 2010;Stalmach et al, 2014).…”
Section: Bioavailability Of Major Coffee Components and Their Metabolmentioning
confidence: 99%